Development of Student/Alumni Content Creator Groups Youth Nutrition for Stunting Prevention in a Stunting Calculator Application: Aplikasi Stunting Calculator - Hayati, Aslis Wirda; Husnan, Husnan; Roziana, Roziana; Pizaini, Pizaini; Akhyar, Amany (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2023)
The problem of stunting adolescents in the world is currently 22.2% or about more than 150.8 million. In efforts to prevent and reduce the prevalence of stunting, it is necessary to provide education to adolescents regarding food consumption in accordance with the rules of balanced nutrition. Community service aims to foster new entrepreneurs based on science and technology, teaching skills by incorporating health sciences through digital training. The book "Balanced Nutrition for Adolescents: Prevent Stunting" has been digitally transformed and integrated into a stunting calculator application on smartphones, enabling adolescents to become content creators. Adolescents are expected to have knowledge about nutrition that will be inputted into the stunting calculator application, understand the preparation for data entry, and utilize the digitized book on a smartphone. The training took place from February to March 2023, comprising five Zoom meetings and one in-person session. There were 23 participants in the training, consisting of students and alumni from the Departments of Nutrition, Nursing, Midwifery, Medical Records, and Informatics Engineering in universities located in Riau and West Sumatra provinces. Each meeting involved assigning tasks to the participants, followed by assessment and discussion at the beginning of subsequent sessions. After the training, participants formed WhatsApp groups for communication and discussion to create content based on their respective interests. The training participants were awarded competence certificates as content creators